2020
DOI: 10.23919/cjee.2020.000008
|View full text |Cite
|
Sign up to set email alerts
|

Capacity configuration of hybrid CSP/PV plant for economical application of solar energy

Abstract: Concentrating solar power (CSP) technology has received increasing attention in recent years because of its distinct advantage for dispatchable power generation from solar energy. However, owing to its highly levelized costs of electricity, CSP plants are less competitive than photovoltaic (PV) power plants. To overcome this drawback and suppress PV power fluctuations, the concept of a hybrid CSP/PV power plant is proposed and developed. A capacity configuration method based on filtering and checking is propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The supply of electricity by hybrid CSP/PV power systems have been proposed by researchers in recent years, as they are expected to combine the characteristics of dispatchable power generation and lower LCOE [5]. It was also shown that by a suitable combination of CSP and PV aiming at a capacity factor higher than 70%, lower costs can be achieved than by increasing storage and solar field size in CSP plants alone [6].…”
Section: Introductionmentioning
confidence: 99%
“…The supply of electricity by hybrid CSP/PV power systems have been proposed by researchers in recent years, as they are expected to combine the characteristics of dispatchable power generation and lower LCOE [5]. It was also shown that by a suitable combination of CSP and PV aiming at a capacity factor higher than 70%, lower costs can be achieved than by increasing storage and solar field size in CSP plants alone [6].…”
Section: Introductionmentioning
confidence: 99%
“…To fulfill electricity demand, many grid operators from different countries have transitioned toward renewable energy sources (RESs) [2] owing to their cost effectiveness and environmental friendliness [3] . Among RESs, solar power systems are popular because of their cost effectiveness [4] , sustainability, and technological maturity [5] . As the power system evolves from centralized generation from oil and gas to distributed generation from RESs [6] , the involvement of power-electronics-based converters is indispensable for ensuring power system stability [7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complementary between solar and wind energy, when wind turbines and photovoltaic power plants are built in a power plant or region, the combined use of wind and solar data can improve the accuracy of prediction [24,25]. When there is CSP in the area, there is a strong trend correlation between CSP and PV power generation [26]. Due to the flexibility of CSP power generation, the uncertainty of photovoltaic power generation and wind power can be weakened to a certain extent [27,28].…”
Section: Introductionmentioning
confidence: 99%